Spell-O-Drama / Mohd Naqiuddin Zulkarnain... [et al.] - Zulkarnain, Mohd Naqiuddin; Bakar, Sulaila; Marzuki, Alim; Mohamed Suhaimi, Ahmad Suhairi; Razali, Azlini (Universiti Teknologi MARA Cawangan Pahang, 2019)
Motivating language learners is very challenging; more so if the language is not his or her mother tongue. Unlike learning one’s mother tongue where it is learnt with no conscious awareness of its grammar pattern, learning a second language or a third is an uphill task. These learners are required to execute mental gymnastics trying to recall all the grammar rules taught to them and only some are able to emerge with a real sense of success. The rest fail! A learner can be successful in acquiring the second language if the learners can be made to realise that a language is a tool communication rather than an object to be analysed. Hence, the learning process of acquiring the language must be enjoyable and active. Spell-O-Drama is a language game developed to not only enhance a learner’s spelling ability but also his comprehension and vocabularies. In order to vouch the effectiveness of the game, questionnaires were distributed to 60 Year Six students from Sekolah Kebangsaan Mahmud in Raub, Pahang. The researchers are inspired to bring forth Spell-O-Drama based on their prior experiences interacting with rural school pupils. Spell-O-Drama is solely developed to spark interest and enjoyment in the pursuit of acquiring English.